Consumers' payment preferences and banking digitalisation in the euro area - Justus Meyer; Federica Teppa (European Central Bank (ECB), 2024)
This paper contributes to understanding consumers' retail payment preferences and digitalisation in personal finances. We focus on the acceptance of cashless payments in everyday situations and the use of mobile banking apps in the euro area, where the payment services market has changed significantly in recent years. In particular, we study app-based tools for day-to-day (offline) purchases that involve small amounts of money as well as digital tools for managing personal finances. By looking at factors associated with using non-cash payment methods, and app-based financial services solutions, we shed light on the topic of financial inclusion in payment services that concern consumers' everyday choices. Using granular microdata from the European Central Bank's Consumer Expectations Survey, we find that most people prefer to use only one payment instrument. After the COVID-19 pandemic, it has mostly been cash and contactless cards. The use of cash is partly due to limited perceived acceptance of non-cash payments by merchants. We also find substantial cross-country heterogeneity and highlight the prominent role of demographic factors in choosing non-cash payment options and app-based tools when managing personal finances. While mobile banking is already popular amongst euro area consumers, the use of smart payment methods remains very limited. Our findings suggest that financial service providers should recognize the growing preference of the younger generations for alternative payment methods. Creating awareness among consumers might also lead to positive feedback effects by reducing consumers' reliance on cash through higher perceived availability of non-cash payment options.
Keywords: C13; D12; E42; O33; 330; Payment Preferences; Cash; FinTech; Digitalisation; Consumer Expectations Survey (CES)